IMPROVEMENT OF 3D GRAPHICS TECHNOLOGIES IN COMPUTER MODELING STUDIES - Yusupova Dilfuzakhon Muhammadqodirovna (Journals Park Publishing, 2022)
3D modeling is a very popular, developing and multi-functional direction in the computer industry today. The creation of virtual models of anything has become an integral part of modern production. Apparently, the release of media products is no longer possible without the use of computer graphics and animation. Of course, specific programs are provided for a variety of tasks in this area. When choosing an environment for three-dimensional modeling, you must first determine the range of tasks that will suit it.
Keywords: modern production; three-dimensional modeling; program